Implementation of the Rough Set Method on Diseases Often Complained of by Patients (Case Study: RSU Raskita) - Syahila, Febby; Sihombing, Marto; Simanjuntak , Magdalena (Devitara Innovations, 2024)
The development of medical technology requires hospitals to be more efficient in providing services, especially in terms of handling diseases that are often complained about by patients. This study aims to identify disease patterns that often appear in Raskita Hospital and provide appropriate treatment priorities based on patient characteristics. Using the Rough Set method, patient data such as age, disease type, and severity are analyzed to find relationships between attributes and determine treatment priorities. This study uses data on diseases that are often complained about by patients at Raskita Hospital in 2023-2024. Diseases such as Dengue Hemorrhagic Fever (DHF), Acute Respiratory Tract Infection (ARI), and Gastroenteritis are identified as diseases that often appear in different age groups, with toddlers and the elderly tending to get higher priority in treatment. By applying the Rough Set method, the decision-making process becomes more effective, especially in determining patient priorities and simplifying complex medical data. The results of the study show that the grouping of attributes based on age range, type of disease, and severity can improve the quality of hospital services. Raskita Hospital can optimize medical resources and provide more appropriate and efficient treatment for patients, especially in dealing with diseases that are often complained about.